Molecular Nature of Marine Particulate Organic Iron-Carrying Moieties Revealed by Electrospray Ionization Fourier-Transform Ion Cyclotron Resonance Mass Spectrometry (ESI-FTICRMS) - Xu, Chen; Lin, Peng; Sun, Luni; Chen, Hongmei; Xing, Wei; Kamalanathan, Manoj; Hatcher, Patrick G.; Conte, Maureen H.; Quigg, Antonietta; Santschi, Peter H. (Frontiers in Earth Science, 2020)
Marine sinking particulate organic matter (POM), acting as a link between surface primary production and burial of organic matter in marine sediments, undergoes a variety of physical and biochemical alterations on its way to the deep ocean, resulting in an increase in its un-characterizable proportion with diagenesis. Further, the binding ligands in POM for iron, an essential nutrient to marine life and tightly coupled with organic matter, has rarely been studied. In the current study, we employed an approach combining sequential extraction with ultrahigh resolution mass spectrometry (ESI-FTICRMS), in order to explore and unravel the chemical characteristics of organic matter compounds relevant to marine particle flux within the mesopelagic and deep ocean, with a focus on the potential iron-carrying molecules. With increasing depth, POM increases in aliphaticity, and decreases in intensity-normalized O/C ratios, aromatics, and carboxylic-rich alicyclic molecules (CRAM)-like compounds. The potential iron-carrying molecules account for ~14% of total identified molecules, and appear to have been incorporated into the marine particles via ion complexation, hydrophobic interaction, and/or interlayered ‘occlusion’. The relative abundance of iron-binding organic molecules in these three operationally-defined categories changes with depth: “surficially-complexed” fraction decreases with depth, the “interlayered-occluded” fraction increases to a comparable extent and “hydrophobic interaction” fraction occurs at all depths. Collectively, the potential iron-carrying organic molecules exhibit a set of unique molecular characteristics: a relatively lower average H/C ratio and a higher O/C ratio compared to bulk POM, a dominance of aromatics, black carbon-like compounds and CRAM-like compounds, and minor amounts of aliphatics. These molecules exhibit partial similar molecular features as precursors formed from photochemical reactions in the surface ocean, but they have been greatly modified by flux processes. Noticeably, a minor fraction of these iron-carrying molecules (<1%) was identified to contain hydroxamate-like moieties (N(OH)-COOH), the key functionality of one of the strongest iron-binding ligands in the dissolved phase. This agrees with improved spectrophotometric results and corroborates their presence in the POM. These hydroxamate-like moieties play an important role in controlling the distributions and fluxes of Fe and particle-reactive radionuclides with similar chemical complexing properties as Fe (e.g., thorium) in the ocean.